Influence of BMI on Serum Adiponectin, Resistine, and FBG among Overweight and Obese Females Diabetic Patient Type2 - Hussein, Salah Eldin Omar; Altoum, Abd Elgadir Alamin; Osman, Ahmed L.; Higazi, Hassan M. K. I.; Ali, Sara; Alfeel, Ayman Hussien (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract: Background and aim: Obesity is a frequent comorbidity in patients with T2DM and it has been estimated that at least 90% of these patients are overweight or obese.[4] The risks of many complications and comorbidities (e.g., cardiovascular disease and chronic kidney disease) are considerably increased in patients with T2DM who have concomitant obesity. In this study evaluation the level of Resistine, Fasting Blood Glucose and Adiponectin in overweight, obese versus normal weight, females. Compare with the BMI. Methods: A descriptive cross-sectional - case-control study, the target population is a total 204 Sudanese females were recruited to participate in this study (102 overweight, obese versus 102 non-overweight, non-obese), aged 20-50 years. and venous blood samples were collected. Plasma levels of blood glucose were measured using the particle-enhanced immunoturbidimetric assay method Cobas C-311®.While Adiponectin and Resistine estimated by ELISA Kits. Anthropometric measurements, including height and weight, were taken using standard protocols. BMI was calculated as weight (in kilograms) divided by height (in meters squared). Results: According to these results observed significant difference between the means of fasting blood glucose (FBG), adiponectin, Resistine and BMI compare with normal weight, overweight and obese respectively. FBG (mean + SD), normal weight (127 ± 16.7), over weight (153 ± 19.2), obese (189 ± 22.7), P = 0.037, adiponectin, (11.2 ± 1.9), (9.7 ± 1.6), (6.1 ± 1.5), P = 0.043, Resistine, (12.8 ± 1.1) ,(14.2 ± 2.7), (18.2 ± 2.9), P = 0.021, BMI, (18.3 ± 1.7) ,(26.1 ± 2.2), (30.4 ± 3.7), P = 0.006. In this study, the results show strong negative Correlation between the levels of serum Adiponectin and Fasting Blood Glucose, Adiponectin and Resistine. (P.value = 0.013, r = -7.9). (P.value = 0.019, r = -6.6). While showing in the other side strong positive Correlation between the levels of serum Resistine and Fasting Blood Glucose. (P.value = 0.015, r = 6.0). Conclusion: Increase of Resistine and Fasting Blood Glucose and reduced of Adiponectin in overweight, obese versus non-overweight, non-obese females. Compare with the BMI. Keywords: Obese, Overweight, BMI, FBG, Adiponectin and Resistine